The TripleSat constellation: a new geospatial data service model. Issue 2 (3rd April 2017) - Wen, Qiang; He, Jianjun; Guan, Shengyong; Chen, Ting; Hu, Yin; Wu, Wenbin; Liu, Feng; Qiao, Yuexia; Yheng Kok, Suet; Yeong, Samuel
Abstract: With the increase of different sensors, applications and customers, the demand from data providers and users is for a new geospatial data service model, which supports low cost, high dexterity, and which would provide a comprehensive service. Based on such requirements and demands, the 21AT TripleSat constellation terminal and data delivery and management system has been developed by a Beijing based high-tech enterprise, Twenty First Century Aerospace Technology Co., Ltd. (21AT). The company is the first commercial Earth observation satellite operator and service provider in China. This new geospatial data service model allows the user to directly access multi-source satellite data, manage the data order, and carry out automatic massive data production and delivery. The solution also implements safe and hierarchical user management, statistical data analysis, and automatic information reports. In addition, a mobile application is also available for users to easily access system functions. This new geospatial solution has already been successfully applied and installed in many customer sites in China, and is now available globally for international clients interested in fast geospatial solutions. It enables the success of customers' operational services. Besides providing TripleSat Constellation images, the multi-source data access system also allows the users to access other satellite data sources, based on customized agreement. This paper describes and discusses this new geospatial data service model.